A Comparative Study of Fibre Composites and Thermoplastics as Rigid Components of Orthoses (Journal of Fiber Bioengineering and Informatics, 2018)
The use of rigid materials to adequately support the joints and exert corrective forces that controlthe deformities of the bones is a key pre-requisite in prescribing custom-fit orthoses in rehabilitationtreatment. Traditional orthotic materials are heavy in weight, bulky and completely unbreathable,which reduce the quality of life, comfort and satisfaction with the orthosis and result in poor patientcompliance and even significant curve progression. The present study aims to explore the use of carbonfibre, fibreglass and fibreglass-carbon composites to develop an orthotic brace. Apart from the mechanicaltesting, the thermal discomfort properties and in-brace pressure with the use of traditional orthotic braceswere also examined. Compared to traditional thermoplastic materials, the fibre composite materials havegood resistance to breakage, more flexibility in bending with improved water vapour transmission, airpermeability and thermal conductivity which advance orthosis use and wear comfort. An increase in thenumber of layers of composite materials increases the bending rigidity and also considerably augmentsthe corrective forces. The corrective forces and ⁄ or support that control the deformity of joints or bonescan therefore be adjusted by altering the number of layers of composites. The use of fibre compositematerials in orthoses not only improves the prevailing problems of wear discomfort, but also facilitatesthe control of corrective forces, thus enhancing the quality of orthotic intervention.